Temporary controls on capital inflows - Reinhart, Carmen M.; Smith, R. Todd; National Bureau of Economic Research (Cambridge National Bureau of Economic Research, 2001)
During the past decade a number of countries imposed capital controls that had two distinguishing features: they were asymmetric, in that they were designed principally to discourage capital inflows, and they were temporary. This paper studies formally the consequences of these policies, calibrates their potential effectiveness, and assesses their welfare implications in an environment in which the level of capital inflows can be sub-optimal. In addition, motivated by the fact that these types of controls have often been left in place after the dissipation of the shock that lead to the controls being implemented, the paper evaluates the welfare cost of procrastination in removing these types of controls.
Keywords: Capital movements; Investments, Foreign -- Government policy; Capital market -- State supervision